Studi Deskripsi Jenis-Jenis Pantun Rejang Dalam Masyarakat Kabupaten Lebong - Eko Anderman; Resnani Resnani; Daimun Hambali (Universitas Bengkulu, 2020)
This study aims to describe the types of rhymes in the Rejang language found in the Lebong community of Bengkulu Province. The approach and type of research used is a qualitative survey. The research locations were Tik Teleu Village, Pelabai, and Kota Baru Santan, Pelabai District, Lebong Regency, Bengkulu Province. Subjects were used as informants. In this study, the traditional leader of Lebong Regency, from Tik Teleu Village and Pelabai Village. Data collection The techniques used in this study were interviews with informants and documentation. Data analysis techniques were data selection, data presentation, conclusion drawing, and data validity test, namely by lengthening observations, increasing persistence, triangulating (triangulating sources) and holding member checks. The results of the study were collected sixty rhymes in the rejang language pantun found in three villages and documentation.The Rejang language is nineteen rhymes from Tik Teleu Village, eighteen rhymes from Kota Baru Santan Village and sixteen rhymes from Pelabai Village and added from the documentation (Book of ireak Ca'o tun Jang) as many as seven rhymes, so there are sixty rhymes. In accordance with the types of rhymes obtained, namely: eleven advice rhymes, five love rhymes, two spirit poems, six traditional rhymes, six religious rhymes, one humorous rhyme, nine figurative rhymes, twelve love rhymes, five proverb rhymes and three puzzles. puzzle. As for the types of Rejang language rhymes that can be used as learning material for local content in elementary schools, there are nine rhymes consisting of eight advice rhymes, two spirit rhymes, five religious rhymes and three puzzle rhymes and one humorous rhyme.